Business process management workshops : BPM 2017 International Workshops, Barcelona, Spain, September 10-11, 2017, Revised papers /: BPM 2017 International Workshops, Barcelona, Spain, September 10-11, 2017, Revised papers. (2018) - Unknown
No abstract available